Phytochemical composition and antioxidant capacity of Psidium guajava fresh fruits and flour - Moreno, María Alejandra (2014)
Psidium guajava fruits are consumed fresh or processed (beverages, syrup, ice cream, jams and jellies). Guayaba is a fruit highly perishable and susceptible to damage during the postharvest. One strategy to overcome this problem is its processing by using techniques that preserve its organoleptic, nutritive and functional properties and allow getting food with added value. The purpose of this study was to obtain flour from fresh fruits cultivated in Argentina Northwestern by lyophilization and to determine the antioxidant activity and the main phytochemicals present in fresh fruits and flour. Nutritional composition (sugar, protein and fat) and the bioactive phytochemicals (total phenolic compounds, flavonoid phenolic, condensed and hydrolizable tannin, ascorbic acid, pigments such as anthocyanin and carotenoids) as well as fiber content, were evaluated. The flour preserved flavor, aroma and color of pulp from fresh fruits. The flour contained around 30% of sugar, 20% of total protein, 0.5% of fat and high level of crude fiber. Carotenoids and ascorbic acid were the dominant phytochemicals in flour as well as in fresh fruits. The guayaba flour showed antioxidant activity with SC50 values similar to fresh fruits. The flour showed nutraceutical characteristics that are demanded by functional food and could be used as a dietary supplement.